2019
DOI: 10.1007/s00382-019-04910-1
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of ocean temperature change to anthropogenic and natural forcings using the temporal, vertical and geographical structure

Abstract: We examine whether significant changes in ocean temperatures can be detected in recent decades and if so whether they can be attributed to anthropogenic or natural factors. We compare ocean temperature changes for 1960-2005 in four observational datasets and in historical simulations by atmosphere-ocean general circulation models (AOGCMs) from the Coupled Model Intercomparison Project phase 5 (CMIP5). Observations and CMIP5 models show that the upper 2000 m has warmed with a signal that has a well-defined geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 89 publications
5
40
0
Order By: Relevance
“…In the multi-model median, temperature in the thermocline is projected to increase on global average by 1.2±0.7°C (Fig. 4b) by the end of the 21st century under the RCP8.5 scenario relative to the period 1861-1959, in accordance with (Levitus et al, 2009(Levitus et al, , 2012Bilbao et al, 2019). Large warming of more than 4.0±0.7°C is projected in the northern North Atlantic and around the subantarctic water in the Indian and Atlantic Oceans (Fig.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…In the multi-model median, temperature in the thermocline is projected to increase on global average by 1.2±0.7°C (Fig. 4b) by the end of the 21st century under the RCP8.5 scenario relative to the period 1861-1959, in accordance with (Levitus et al, 2009(Levitus et al, , 2012Bilbao et al, 2019). Large warming of more than 4.0±0.7°C is projected in the northern North Atlantic and around the subantarctic water in the Indian and Atlantic Oceans (Fig.…”
supporting
confidence: 52%
“…In the eastern tropical Atlantic, the spread for ToE rel (O 2 ) is, despite a smaller global mean spread, larger than for ToE rel (T). In summary, even though the median pattern of ToE rel (O 2 ) is relatively uniform in comparison to 5 ToE rel (T), the spread for ToE rel (O 2 ) varies between regions as for ToE rel (T).…”
Section: Relative Time Of Emergencementioning
confidence: 87%
See 2 more Smart Citations
“…We use only one observational dataset Levitus et al (2012), as results from other detection and attribution studies shown to be relatively insensitive to the use of other observational data sets (Gleckler et al 2012, Bilbao et al 2019, Slangen et al 2014. The Levitus et al (2012) dataset provides a raw (non-interpolated) three-dimensional ocean temperature data set, which is needed for detection and attribution analysis presented here (figure S6).…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%